Homage to Proserpina, or: why did the charophytes of the Pergusa Lake vanish? - Angelo Troia (Edizioni Danaus, 2020)
An important bisexual population of the charophyte Chara canescens Loisel. (Characeae, Charales, Charophyceae) was reported in the XIX century for the Pergusa Lake (Sicily). A recent field survey to check its presence revealed that it has disappeared. After a bibliographic research to understand when and why this happened, the input of freshwater from outside the basin and the introduction of the carps were identified as the two main causes for its recent extinction. Some possible management measures to try to restore the lake ecosystem are proposed.